Microstructure and mechanical properties of as-extruded AZ80–xSn magnesium alloys. Issue 18 (11th December 2016) - Jiang, L. Y.; Zhang, D. F.; Fan, X. W.; Guo, F.; Xue, H. S.; Pan, F. S.
Abstract : The effect of 0–2 wt-% Sn addition on AZ80 magnesium alloys after 350°C extrusion has been studied by analysing microstructure and mechanical properties. The results indicated that dynamically recrystallised grains were fine and homogeneous with less than 1 wt-% Sn addition. In AZ80–0.5Sn alloy, a large number of Mg17 Al12 precipitated phases formed in grains and at grain boundaries during extrusion process. With more than 1 wt-% Sn addition, the size of dynamically recrystallised grains increased and the number of Mg17 Al12 phases decreased. The strength of as-extruded AZ80–0.5Sn alloy enhanced largely as compared with that of the as-extruded AZ80 alloy. AZ80–0.5Sn alloy had the outstanding tensile and compressive properties.